Anti-Vaxxers-Grounds for assertion of fundamental rights under the constitution / Azlina Mohd Hussain and Dr. Nor Syamaliah Ngah - Mohd Hussain, Azlina; Ngah, Nor Syamaliah (UiTM Cawangan Negeri Sembilan, 2022)
The CCMD-19 pandemic brought with it the necessary challenges in all facets of life. Most importantly, now, that is being hotly debated and vigorously challenged is the mandatory regulation of vaccination for the COVID-19 virus. Various grounds have been propagated by anti-vaccination campaigners also known as "anti-vaxxers" to restrain the rapid progression of vaccination. Most important grounds lie in, of course the fundamental rights under the constitution. This article wishes to examine to what extent can the fundamental liberties provisions under the constitution can be stretched to cover protection against the mandatory vaccination mandate. Grounds Under the Constitution - Anti-vaxxers have used various grounds to dodge the mandatory regulation for vaccination. This protest has been going on for as far as the vaccine for COVID-19 has been developed but the ultimate showdown came in mid-2021 when the vaccine was introduced officially and administered on the world population. The World Health Organization (WHO) has sanctioned the almost compulsory mandate that all should be vaccinated against this virus. The vaccine issue has covered economic, political, medical, law, moral and ethical issues. The administration of the vaccine had been widely debated. Most are sceptical as to its effectiveness, its relevance and need. Whilst most medical experts have assured its safety yet there will always be some who do not agree. What is really being protested is not clear, yet from the literature, it would seem that most of the protest is in relation to the "mandatory" regulation that requires all to be vaccinated.